Juridical Analysis of Legal Considerations of Constitutional Court Judges Number: 46/PUU-VIII/2010 Review of Article 43 (1) of Law Number 1 of 1974 concerning Marriage Regarding the Status of Children Out of Wedlock - Agung Dwi Prayogo; Nuria Siswi Enggarani (Proceeding International Conference Restructuring and Transforming Law, 2023)
This investigation was carried out with the aim of proving the decision of the Constitutional Court regarding illegitimate children, in accordance with Law no. 46/PUU-VIII/2010, consideration of the Constitutional Court: Regarding the status of illegitimate children, see Law no. 46/PUU-VIII/2010 and its legal impact on the occurrence of the Constitutional Court Order regarding Article 43 paragraph 1 of the Marriage Law which regulates invalid marriages that produce children. The method used is normative legal research, namely an in-depth study of literacy related to the status of illegitimate children. The Constitutional Court's decision regarding the civil rights of children born out of wedlock is a decision that emerged from monitoring the rights of illegitimate children as a form of judicial review of marriage law. Children born from illegitimate marriages are not a matter of Constitutional Court decision no. 46/PUU-VIII/2010. This decision is an option that significantly affects the social freedom of illegitimate children. The novelty of this research lies in the research based on a phenomenon that often occurs today, namely the problem of pregnancy outside of marriage.